Respostas
respondido por:
1
f(-2) = -5
-2a + b = -5
f(x) = 5
a + b = 5
Faça um sistema:
-2a + b = -5
a + b = 5
Multiplica a segunda por -1
-2a + b = -5
-a -b = -5
-3a = -10 (-1)
3a = 10
a = 10/3
Se a é 10/3 então b é:
a + b = 5
10/3 + b = 5
b = 5 - 10/3
b = 5/3
Descobrir f(1/2):
f(1/2) = 10x/3 + 5/3
f(1/2) = 5/3 + 5/3
f(1/2) = 10/3
acho que é isso, se eu estiver errado me corrija e me desculpe
-2a + b = -5
f(x) = 5
a + b = 5
Faça um sistema:
-2a + b = -5
a + b = 5
Multiplica a segunda por -1
-2a + b = -5
-a -b = -5
-3a = -10 (-1)
3a = 10
a = 10/3
Se a é 10/3 então b é:
a + b = 5
10/3 + b = 5
b = 5 - 10/3
b = 5/3
Descobrir f(1/2):
f(1/2) = 10x/3 + 5/3
f(1/2) = 5/3 + 5/3
f(1/2) = 10/3
acho que é isso, se eu estiver errado me corrija e me desculpe
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás
10/6 (e não 10/5) + 5/3